ANALISA SIFAT MEKANIS BAJA ASSAB 760 YANG MENGALAMI PROSES TEMPERING DENGAN VARIASI SUHU PEMANASAN - Lutfi; Unung Lesmanah; Nur Robbi (Jurnal Teknik Mesin, 2016)
From machine parts, often found a subtance that required hardness and ductility. 760 ASSAB steel is carbon steel that has a carbon steel around 0,30% - 0,60% as well as classified as medium carbon steel. 760 ASSAB steel widely used as the material production of automotive component, where in steel production are used as tools and utensils, crankshaft, bolt, gear in motor vehicles. To improve the hardness and ductility of the steel through the process of tempering with temperature variation ( 200C, 400C, 600C ) and tempering after hardening ( 950C ) the cooling medium used is water. Test equipment hardness and toughness with vickers and methods charpy. The result obtained from this research that the tempering temperature of 200C with the hardness value 156.7 HVN and toughness 1.586 joule / mm2. Tempering temperature 400C with a hardness value 183.5 HVN and toughness 1.584 joule / mm2. Tempering temperature 600C with a hardness value 182.2 HVN and toughness 1.583 joule / mm2. Hardening after the tempering temperature 950C with a hardness value 175.8 HVN and toughness 1.585 joule / mm2